Typology analysis and correlation between poverty, health, and education in central kalimantan - Rini Hastuti; Alexandra Hukom (Institute of Computer Science (IOCS), 2023)
The poverty rate in Central Kalimantan in the last period has shown an increase in contrast to education and health data which show a positive trend. This is far from the Regional Action Plan that has been designed, so it is necessary to carry out an analysis to determine the relationship between several research variants. This study aims to analyze the correlation and mapping of the poverty quadrant region with district/city levels of education and health in the Province of Central Kalimantan in 2018 and 2021. This research is a type of quantitative research using secondary data which is analyzed through Cartesian diagrams and Pearson correlations. The population and research samples cover 14 districts/cities in the Province of Central Kalimantan. The results showed that there were four areas of poverty, education and health quadrants. A comparison of the mapping of the quadrant areas between poverty and education in 2018 and 2021 shows no difference, while the quadrant areas of poverty and health in 2018 and 2021 show a shift. The Pearson correlation test conducted on the variables of poverty, education, and health shows a negative relationship but low correlation or in other words there is no strong influence between variables. The implication of the findings of this study is that there is a need for policies from the government as policy makers to create educational programs that tend to increase skills. Not only that, special attention is needed to improve health quality in Central Kalimantan Province so that it can become a poverty alleviation tool.